Pengembangan Theopreneurship di Muhammadiyah: Studi di Pesantren Darul Arqom Patean Kendal dan Pesantren Al-Mu’min Tembarak Temanggung - Miswanto, Agus; Nugroho, Irham; Suliswiyadi, Suliswiyadi; Kurnia, Marlina (Jurnal Tarbiyatuna, 2019)
This research is about theopreneurship of pesantren. Theopreneurship is a relatively new study in the academic world, namely entrepreneurship based on religious values, which is rather different from entrepreneurship studies in general. This research is a descriptive analysis; for collecting data using the in-depth interview method and Focus Group Discussion (FGD). From the research it was found that the two pesantren of Muhammadiyah, namely al-Mu'amin Tembarak and Darul Arqom Patean used the Kulliyatul Mu'allimin al-Islamiyyah (KMI) model in the management of student learning, namely daily learning management for students for 24 hours of full day in the boarding schools. For the development of theopreneurship, Darul Arqom Patean uses the organizational culture formed in the pesantren environment, namely business development through a business division that was formed institutionally and the development of santri entrepreneurship motivation through the Darul Arqom Organization students (OSDA). Meanwhile, pesantren al-Mu'min Tembarak, entrepreneurship development has not yet become an organizational culture, pesantren is still looking for models and forms. For the development of the entrepreneurial ethos of students carried out through the organizational culture of the Muhammadiyah Student Association (IPM).